The Prevalence of Fibroma in Oral Mucosa Among Patient Attending USM Dental Clinic Year 2006-2010 - Daddy Suradi Halim; Abdullah Pohchi; Pang EE Yi (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
The purpose of this preliminary retrospective study was to determine the prevalence of fibroma in oral mucosa among patients attending USM dental clinic from 1/6/2006-1/6/2010. Fibroma of the oral mucosa is the most common benign tumor of the oral cavity. It is a reactive hyperplasia of fibrous connective tissue in response to local irritation or trauma. A lesion on any part of the oral mucosa have a broad differential diagnosisranging from traumatic lesions (mucocele), neurogenic lesions (neurofibromatosis), lipoma , epithelial tumors (squamous papilloma) and inflammatory/reactive hyperplasia of soft tissue (pulp polyp). A total number of 192 patients (82 male and 110 female) who are registered in the Oral Medicine and Oral Pathology Log Book were included in this study regardless of their age, 16 % of them were diagnosed to have fibroma and out of that, 29% of them were male and 79% female. The peak incidence of the lesion was in the 3rd decade of life. The lesions occurred in the tongue, lip mucosa, sulcus region and buccal mucosa were each to be 12.9%, 12.9% , 32.2 % and 41.9%. This study shows that fibroma is one of the common oral mucosal lesion and it occurred mostly in the 3rd decade of life where the prevalence is higher in female patients.